HEROISM AND ANTI-HEROISM AS REFLECTED IN THE CHARACTER OF JAKOB HEYM IN JUREK BECKER'S "JAKOB - THE LIAR" AND THE CHARACTER OF GEORG HEISLER IN ANNA SEGHERS' "THE SEVENTH CROSS" (Journal of Foreign Language Studies, 2024)
.